Adessowiki: Collaborative scientific programming environment - Rittner L. (2011)
Adessowiki is a collaborative environment for teaching and research in image processing. Adessowiki is composed of a collection of collaborative web pages in the form of a wiki. The articles of this wiki can embed programming code that will be executed on the server when the page is rendered, incorporating the results as figures, texts and tables on the document. The integrated collaborative environment of Adessowiki, containing documentation, programming code and execution results is able to create several possibilities of applications. This paper presents some of the applications where Adessowiki has been used, such as Scientific Writing and Virtual Learning Environment. © 2011 IEEE.